Graphene-loaded left-handed media for tunable electromagnetic surface waves. Issue 13 (2nd September 2021) - Yaqoob, M. Z.; Ghaffar, A.; Naz, M. Y.; Hanif, M. A.
Abstract : Theoretical investigation has been carried out on the tunable electromagnetic surface waves propagating along the Graphene loaded semi-infinite left-handed media (LHM) interface. The analytical modeling of the graphene has been done in the frame work of Kubo's formulation. The split ring resonators (SRRs) model and Kramers-Kronig relations-based causality principle have been used to simulate the GHz-LHMs and THz-LHMs respectively. To realize the graphene loaded LHM interface, the impedance boundary conditions (IBCs) have been employed. The dispersion curves, effective mode index, propagation length, penetration depth, phase velocity and fields profiles of surface waves supported by graphene loaded GHz-LHM and THz-LHM have been computed numerically. It has been concluded that the graphene parameters can be used to tune the characteristics of surface waves in GHz and THz range. The proposed study may have potential applications in designing the near field imaging platforms, communication devices and tunable surface wave guides.